ETHOAHTPOПOЗYM/Ethnoanthropozoom: Journal of the Department of Ethnology, Institute of Geography, Faculty of Natural and Mathematical Sciences, University of St. Cyril and Methodius, Skopje, Makedonie 2/2002-3/2003. - Janeček, Petr (Lidé města, 2006)
A review of the book.